A preliminary report of exploration of the exosomal shuttle protein in marine invertebrate Chlamys farreri. Issue 131 (December 2022) - Wang, Lihan; Zhao, Dianli; Han, Renmin; Wang, Yan; Hu, Jingjie; Bao, Zhenmin; Wang, Mengqiang
Abstract: Exosomes are extracellular vesicles secreted by diverse cell under normal or abnormal physiological conditions, which could carry a range of bioactive molecules and play significant roles in biological processes, such as intercellular communication and immune response. In the current study, a preliminary study was performed to investigate the exosomal shuttle protein in Chlamys farreri (designated as C f esPro) and to predict the potential function of exosomes in scallop innate immunity. The serum derived exosomes (designated as C f EVs) were obtained from lipopolysaccharide (LPS)-stimulated C. farreri and untreated ones. After confirmation and characterization by transmission electron microscopy (TEM), nano-HPLC-MS/MS spectrometry was performed on C f EVs using a label-free quantitative method. Totally 2481 exosomal shuttle proteins were identified in C f EVs proteomic data, which included many innate immune related proteins. GO and KOG functional annotation showed that C f esPro participated in cellular processes, metabolism reactions, signaling transductions, immune responses and so on. Moreover, 1421 proteins in C f esPro were enriched to 324 pathways by KEGG analysis, including several immune-related pathways, such as autophagy, apoptosis and lysosome pathway. Meanwhile, eight autophagy-related proteins were initially identified in C f esPro, indicating that C f EVs had a potential role with autophagy. All these findings showed that C f EVs were involved in C. farreri innate immune defenses. This research would enrich the protein database of marine exosomes and provide a basis for the exploration of immune defense systems in marine invertebrates. Highlights: Serum derived exosomes in Chlamys farreri ( Cf EVs) were isolated and analyzed using LC-MS/MS techniques. Totally 2481 exosomal shuttle proteins ( Cf esPro) were identified in Cf EVs proteomic data. Innate immunity and autophagy related proteins were identified Cf esPro.